MENELUSURI OPNINI AUDITOR INDEPENDEN ATAS LKPD PEMERINTAH PROVINSI BALI - BUDIARTHA, KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009))
The financial report of a district government is are report showing its financial performance within one budgeting period. The Public Sector Auditor (BPK) is in charge to audit the report before going to be accountable toward the legislative. As shown by the result of an audit, whether its financial performance is good or not, depended upon the opinion given by the Public Sector Auditor (BPK). According to the audit conducted on the financial report of government province of Bali for year 2005, indeed the BPK issued Qualified Opinion; which means it is still that the report of the government of province of Bali applying inconsistently with the rule and relevant statutory is all material aspects.
Keywords: BPK, LKPP, LKPD, auditor independent opinion, SPKN, SAP